Premenstrual disorders and risk of sick leave and unemployment: a prospective cohort study of 15 857 women in Sweden - Sara Hägg; Alicia Nevriana; Donghao Lu; Hang Yu; Unnur Anna Valdimarsdottir; Yihui Yang; Elgeta Hysaj; Elizabeth Bertone-Johnson (BMJ Mental Health)
Background Premenstrual disorders (PMDs) are prevalent and impair women’s quality of life, but their long-term influence on work capacity is unclear. Understanding the association between PMDs and subsequent sick leave and unemployment could inform interventions and policies.Objective We hypothesised that women with PMDs have an increased risk of future sick leave and unemployment compared with those without PMDs.Methods We conducted a prospective cohort study involving 15 857 women aged 15–60 years who were employed at baseline in the LifeGene Study, with linkage to population and health registers in Sweden. PMDs were identified from clinical diagnoses and symptom questionnaires; sick leave and unemployment data were obtained from national registers. Poisson regression estimated incidence rate ratios (IRRs) for sick leave and unemployment in women with versus without PMDs.Findings A total of 2585 (16.3%) women (mean age 32.5 years) had probable PMDs. Over a median 9.17-year follow-up, 6741 (42.5%) and 1485 (9.4%) experienced at least one sick leave or unemployment, respectively. Compared with women without PMDs, those with PMDs had a 40% higher risk of sick leave (IRR 1.40, 95% CI 1.31 to 1.49) and a 27% higher risk of unemployment (IRR 1.27, 95% CI 1.10 to 1.46). Risk elevations were pronounced for sick leave≥90 days (IRR 1.69, 95% CI 1.50 to 1.91) and depression-related sick leave (IRR 1.41, 95% CI 1.27 to 1.56).Discussion Women with PMDs are at increased risk of sick leave and unemployment, suggesting significant long-term socioeconomic burden associated with PMDs.Clinical implications This study underscores the need for greater awareness of PMDs in clinical practice. Healthcare providers should recognise the potential impairment at work associated with PMDs, especially in women with recurrent symptoms or comorbidities like anxiety or depression.